2019
DOI: 10.1055/a-0882-6545
|View full text |Cite
|
Sign up to set email alerts
|

Aktuelle Entwicklungen in der regionalen Behandlung von peritonealen und pleuralen Tumoren (inkl. HIPEC und HITOC)

Abstract: ZusammenfassungDie multimodale Therapie von begrenzten peritonealen Metastasen kann bei ausgewählten Tumorentitäten die Prognose der Patienten günstig beeinflussen, sollte eine komplette Resektion erfolgen (Pseudomyxoma peritonei, malignes peritoneales Mesotheliom, kolorektales Karzinom, Magenkarzinom und Ovarialkarzinom). Oft wird additiv eine hypertherme intraperitoneale Chemotherapie (HIPEC) intraoperativ durchgeführt. Wenn die Behandlung in erfahrenen (und zertifizierten) Zentren durchgeführt wird, ist die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…However, these results should be cautiously interpreted due to the limited number of included patients. A previous study showed that about 60% of patients with pleural metastases are secondary to extra thoracic malignancies, with breast cancer as the most common primary with incidence about 25% followed by lymphoma (10%), ovarian cancer (5%), and intraabdominal malignancies (5%) (18). The complete surgical cytoreduction of metastatic ovarian cancer in the abdominal cavity was shown to be an independent prognostic factor, however the role of CRS in thoracic cavity has scarcely been reported…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results should be cautiously interpreted due to the limited number of included patients. A previous study showed that about 60% of patients with pleural metastases are secondary to extra thoracic malignancies, with breast cancer as the most common primary with incidence about 25% followed by lymphoma (10%), ovarian cancer (5%), and intraabdominal malignancies (5%) (18). The complete surgical cytoreduction of metastatic ovarian cancer in the abdominal cavity was shown to be an independent prognostic factor, however the role of CRS in thoracic cavity has scarcely been reported…”
Section: Discussionmentioning
confidence: 99%
“…The main finding of our study was a prolonged survival in selected patients with secondary pleural metastases after CRS+HITOC as a part of multimodal treatment approach with median overall survival of 39 months and median RFS/PFS of 14 months. Retrospective studies showed an encouraging survival of patients with pleural mesothelioma or thymus tumours with pleural involvement, who underwent a multimodal treatment approach including local interventions with CRS+HITOC ( 5 , 11 , 20 ). However, there is paucity of studies investigating the outcome of CRS+HITOC in patients with secondary pleural metastases as a part of multimodal concept.…”
Section: Discussionmentioning
confidence: 99%
“…Der Einsatz chirurgischer Ansätze bei der Peritonealkarzinose und der Pleurakarzinose hat sich weiter konsolidiert, und die Indi-kationen, in denen das Verfahren mit gutem onkologischen Outcome durchgeführt werden sollte, wurden im Vergleich zu vor einigen Jahren weiter eingeschränkt [4]. In der vorliegenden Ausgabe stellen Piso und Koautoren in diesem Zusammenhang die Position der ACO, der Association Chirurgische Onkologie der DGAV (Deutsche Gesellschaft für Allgemein-und Viszeralchirurgie, http://aco-chirurgie.de/) zur aktuellen PRODIGE-7-Studie dar [5].…”
unclassified